Thematic Ethno-Edutainment Learning to Improve Student’s Concept Understanding in Science - Ardianti, Sekar Dwi; Wanabualiandari, Savitri; Tanghal, Analiza B. (Asian Journal of Applied Education (AJAE), 2023)
This study determined the enhancement of students' conceptual understanding in science through subject-based learning in ethno-edutainment and to identify aspects of ethno-edutainment that improve students' conceptual understanding of subject-based learning. It employed a mixed method with a sequential explanatory design variant that combines quantitative and qualitative data. Data gathering techniques in this study consisted of a quantitative data testing technique with analysis using normality gains tests and interviews and a qualitative data observation technique with qualitative descriptive analysis. The analysis of four primary schools in Kudus province showed that students' average conceptual comprehension ability rose from the starting value of 63.4 to 86.7, so the interpretation of learning improvement was moderate.The study concluded that there was moderate improvement among the four primary schools in Kudus Province and that students had average conceptual comprehension. Furthermore, respondents showed appreciation for gamification elements and already had knowledge of the local culture.